The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5694/mja2.51166
|View full text |Cite
|
Sign up to set email alerts
|

Public mental health service use by people with intellectual disability in New South Wales and its costs

Abstract: ental health disorders are the largest contributors to the non-fatal burden of disease in Australia 1 and are a leading cause of morbidity. Rates of mental health disorders are higher among people with intellectual disability than for the general population. [2][3][4][5] Nevertheless, the drivers of mental health service use by people with intellectual disability are unknown. Better understanding of their health needs is critical for responding to the recent finding by the Royal Commission into Violence, Abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…People with intellectual disability have high health needs that require frequent use of acute health care services such as emergency departments and hospitalisations [ 1 , 2 ]. People with intellectual disability often experience poor quality of care and inefficiency of care in these settings [ 3 , 4 ], which contribute to reattendance at emergency departments, and readmission within close proximity to discharge [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with intellectual disability have high health needs that require frequent use of acute health care services such as emergency departments and hospitalisations [ 1 , 2 ]. People with intellectual disability often experience poor quality of care and inefficiency of care in these settings [ 3 , 4 ], which contribute to reattendance at emergency departments, and readmission within close proximity to discharge [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respondents in both age-groups reported higher level of anxiety than the general Australian population, and prevalence of depression was higher than the general population in the older-aged group (Australian Bureau of Statistics, 2018b). Previous studies have found that up to a third of people with intellectual disability have a co-existing psychiatric illness (Mazza et al, 2020;Morgan et al, 2008), and are higher users of mental health services (Srasuebkul et al, 2021). Conditions that have previously been shown to be associated with intellectual disability at higher rates than the general population include schizophrenia and unspecified psychiatric disorders (Mazza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The intellectual disability health sector in Australia has strong roots in primary care, where a lot of early research and pivotal work around the utility of health assessments was undertaken (e.g., Lennox et al, 2010). More recent research has focused on understanding knowledge and skill gaps in our health workforce (e.g., Cashin et al, 2022) and describing how people with intellectual disability use our health system to inform service planning (e.g., Srasuebkul et al, 2021). Groundwork, including Medicare reimbursement and collation of evidence of effectiveness, has been laid to support routine application of comprehensive annual health assessments by GPs.…”
Section: An Emerging Evidence Base For Healthcare For People With Int...mentioning
confidence: 99%